2020
DOI: 10.3389/fsoc.2020.00064
|View full text |Cite
|
Sign up to set email alerts
|

Transgender and Non-binary Swimming in the UK: Indoor Public Pool Spaces and Un/Safety

Abstract: This paper draws from the findings of research that was initiated as a consequence of previous research activities related to University-LGBT community physical activity projects (2012–2018). Specifically, the research underpinning this paper centers transgender and non-binary experiences of recreational swimming and aquatic activity (2017–2020). To date, the research has received small amounts of funding from four sources and resulted in two public engagement activities (two art exhibitions). The findings tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Previously, when writing about research with, by and for LGBT individuals, I have critically discussed the historical socio-cultural naming and labeling of sexualities (Caudwell, 2015a, 2015b), and the complexities of lived experience within the term LGBT in relation to transgender (Caudwell, 2014); referring to self-identification (Caudwell, 2020). Notwithstanding identity politics and the value of the terms lesbian, gay, bisexual and transgender to equality, inclusion and social justice, there is a need for a deeper discussion regarding transgender and non-binary existence from an ontological and epistemological point of view.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, when writing about research with, by and for LGBT individuals, I have critically discussed the historical socio-cultural naming and labeling of sexualities (Caudwell, 2015a, 2015b), and the complexities of lived experience within the term LGBT in relation to transgender (Caudwell, 2014); referring to self-identification (Caudwell, 2020). Notwithstanding identity politics and the value of the terms lesbian, gay, bisexual and transgender to equality, inclusion and social justice, there is a need for a deeper discussion regarding transgender and non-binary existence from an ontological and epistemological point of view.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of my embodied self, I do not normally face everyday, frequent and deliberate scrutiny, surveillance and suspicion. (Caudwell, 2020, p. 4)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the community partnership between Claire Carter with the University of Regina, Common Weal Community Arts organization, and instructors with FadaDance Troupe, the analysis provided involves two projects: the first, a pilot study entitled Queering Dance, which involved three dance workshops in 2018, and the second, a current SSHRC Connections Grant project, called Queering Dance, Moving Communities, which builds on the pilot to offer training and mentorship in trans/non-binary/genderqueer dance and choreography as well as community workshops led by local, national, and international trans/non-binary/genderqueer experts. Previous research on the relationship between queer exercise spaces and gender, body image, and community reveals that trans/genderqueer/queer individuals experience exclusion, discrimination, and discomfort in community leisure spaces as well as a desire to be more grounded in their bodies (Carter, 2021;Caudwell, 2020; Sykes, 2010). Our collaboration endeavours to provide a space for participating individuals to be in and with their bodies in new and creative ways, to embody gender/queerness, meet other gender/queer individuals, and enhance community building.Central to the pair of sequential projects discussed here, has been a focus on establishing programming and space in support of trans and queer community well-being in Regina, sustained by community engagement and consultation, research team reflexivity and training, and relationship building between artists, community organizations, and the university.…”
mentioning
confidence: 99%
“…There are many factors that inform the lack of engagement in leisure programming and spaces by 2SLGBTQIAP+ community members that range from change-rooms politics and heightened bodily visibility, to issues of accessibility informed by transphobia, colonialism, ableism, racism, homophobia, and fatphobia (Brackenridge et al, 2007). Specifically, Caudwell (2020) found that "transgender and nonbinary people face a set of inequalities when it comes to physical activity participation… [and] these inequalities impact on participation rates" (p. 3).…”
mentioning
confidence: 99%